2008
DOI: 10.1111/j.1365-2672.2007.03634.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungi and selected mycotoxins from pre- and postfermented corn silage

Abstract: Aim:  To determine fungal genera, Aspergillus and Fusarium species and aflatoxin B1 (AFB1), zearalenone (ZEA), deoxynivalenol (DON), fumonisin B1 (FB1) contamination from pre‐ and postfermented corn silage produced in the most important region of Argentina where silage practice is developed. Methods and Results:  Sampling of corn silos was performed manually through silos in transects at three levels: upper, middle and low sections. AFB1 and FB1 were quantified by high‐performance liquid chromatography, zearal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
45
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 26 publications
15
45
1
Order By: Relevance
“…The results of differences in DM%, pH and a W values for seasonal samples are comparable to those obtained by Keller et al 33 in Brazil and González Pereyra et al 34 in Argentina.…”
Section: Discussionsupporting
confidence: 78%
“…The results of differences in DM%, pH and a W values for seasonal samples are comparable to those obtained by Keller et al 33 in Brazil and González Pereyra et al 34 in Argentina.…”
Section: Discussionsupporting
confidence: 78%
“…According to the mycological quality criterion 56% (26/46) samples could be qualified as good, 7% (3/46) as regular, and 37% (17/46) as bad (on DRBC). In Argentina there is information about the mycobiota and natural occurrence of mycotoxins in feedstuff [1924, 32, 36, 37]. However these reports on poultry feed refer mostly to Córdoba and Entre Rios provinces (central area of the country).…”
Section: Resultsmentioning
confidence: 99%
“…Aspergillus fumigatus is a widely distributed saprophytic fungus that can be found in the soil or decaying organic matter where it performs an essential role in the carbon and nitrogen cycle. Previous studies have shown the prevalence of Aspergillus species in silage and finished feed for cattle in feedstuffs (González Pereyra et al 2008, 2011Pereyra et al 2008;Keller et al 2012;Alonso et al 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…If this process does not occur in the proper conditions it could lead to the growth of yeasts that increase the pH followed by an increase in temperature. If the pH increases above the critical limits, the development of other microorganisms that spoil the silage such as Aspergillus species, one of the most common genera isolated in silage, can occur (Weissbach 1996;El-Shanawany et al 2005;Garon et al 2006;González Pereyra et al 2008;Alonso et al 2013). Aspergillosis is defined as the tissue damage caused by fungi of the genera Aspergillus (Vanden Bossche 1988).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%